Welfare impacts of seasonal maize price fluctuations in Malawi - Chiwaula, Levison; De Weerdt, Joachim; Duchoslav, Jan; Goeb, Joseph; Gondwe, Anderson; Jolex, Aubrey (International Food Policy Research Institute, 2024)
Maize prices fluctuate significantly throughout the year in Malawi, creating winners and losers depending on who is selling and who is buying the staple at different times. We link maize market price data to nationally and temporally representative household survey data on maize sales and purchases to quantify welfare gains and losses throughout the year. A stable maize price would lead to only a modest increase in Malawi’s total social surplus when summed across a whole year, but a dramatic reduction in hunger during the lean season. We discuss policy options to smooth maize prices throughout the year.